Adaptation of the Land Use System as One of the Main Paradigms of the Modern Agricultural Land Use - Mikhailovich Rogatnev, Yuri; Nikolaevna Scherba, Valentina; Vladimirovna Marakaeva, Tatyana; Viktorovna Nozhenko, Tatyana; Alexandrovna Kapitulina, Natalia (International Journal of Engineering and Technology, 2018)
The article reveals one of the main paradigms for the agricultural land use development. Adaptation is not only a necessity, but a means to improve sustainability and efficiency in the use of agricultural land. The conditions of external systems that determine the direction and magnitude of adaptation options for agricultural land use have also been shown. The features of adaptation of the basic land use elements have been described: land plots, legal status, engineering equipment of the territory, land use system, and land use maintenance system. The article provides aÂ more detailed overview of the adaptation of the main land use system element (agriculture), which will ensure the adaptation of crops and their varieties to the features of soils and terrain; the adaptation of cultivation technologies to the soil and terrain, the features of the territory; the adaptation of fertilizer systems to soils and crops and their varieties; the adaptation of cultivation technologies to the actual technical equipment; the adaptation of the farming system to the actual financial condition; and the adaptation of the farming system to the natural conditions of the year. A monographic description of the land use adaptation experiment by Chistoe, LLC in the Tyukalinsky District of the Omsk Region has been produced. Mutual adaptation of both land management and its technical and technological components has been proposed for the agricultural land development project. It is expected that this will minimize the required financial costs by adapting land properties, reducing types of machines and the technologies used.Â Â